Quantifying the Curvature of Curves: An Intuitive Introduction to Differential Geometry. Issue 2 (7th February 2021) - Osborne, Jason M.; Cook, William; Bossé, Michael J.
Abstract : In this paper we introduce the reader to a foundational topic of differential geometry: the curvature of a curve. To make this topic engaging to a wide audience of readers, we develop this intuitive introduction employing only basic geometry without calculus and derivatives. It is hoped that this introduction will encourage many more to both consider this mathematical notion and to develop enthusiasm for mathematical studies.